Thermoanalytical study of nimesulide and their recrystallization products obtained from solutions of several alcohols - Gálico, D. A. [UNESP]; Perpétuo, G. L. [UNESP]; Castro, R. A E; Treu-Filho, O. [UNESP]; Legendre, Alexandre de Oliveira [UNESP]; Galhiane, Mario Sergio [UNESP]; Bannach, Gilbert [UNESP] (Springer Nature, 2013)
Thermogravimetry, differential scanning calorimetry, and vibrational infrared spectroscopy were used to study nimesulide and its recrystallization products that were obtained from solutions of several alcohols. The thermoanalytical measurements were performed in both air and nitrogen atmospheres and the results suggest that, under the experimental conditions used in this paper, it was possible to obtain neither polymorphic nor pseudopolymorphic forms of this drug. In this investigation, quantum chemical approach methods were used to determine the molecular structures using the Becke three-parameter hybrid method and the Lee-Yang-Parr correlation functional. The performed molecular calculations were done with the Gaussian 09 routine and the theoretical calculation results were correlated with the experimental IR vibrational spectrum. © 2013 Akadémiai Kiadó, Budapest, Hungary.
Keywords: Infrared spectroscopy; Nimesulide; Polymorphism; Theoretical calculations; Thermal behavior